Morphological and growth profile study of blastocystis spp. from stool sample of cattles - Mohammad, Mardhiah; Kamaruddin, Site Kasmadiana (2018)
Blastocystis sp. is protozoan parasites that can cause gastrointestinal disorder in human and animal. The study on Blastocystis sp. is rising due to lack of standardized diagnosis and possibility of harmful strains of the organisms (Barua et al., 2015). In Malaysia, the study on cattle was limited. Therefore, this study was aimed to determine morphological and growth profiles of Blastocystis sp. isolated from 10 positive samples obtained from stool of cattles cultured in Jone’s medium supplemented with inactivated horse serum for 10 days. Upon microscopy examination of Blastocystis sp. viable cells, cyst and vacuolar forms were commonly observed followed by granular and amoeboid. The different forms has appeared in consecutively manner and growth profiles indicated a high peak of parasite counts from day 4 till 7. The highest numbers of cyst (26.16 x 104 cells ± 5.44) were observed on day 2, whereas vacuolar (17.8 x 104 cells ± 1.72), granular (0.88 x 104 cells ± 0.70) and amoeboid forms (1.92 x 104 cells ±0.76) on day 6. The results were useful for detection of different forms of Blastocystis sp. in short period of culture and shall be uttilized for futher investigation in understanding the zoonotic potential and its pathogenicity.